PENGARUH OPTIMISME TERHADAP ADVERSITY QUOTIENT PADA MAHASISWA YANG BEKERJA DI UNIVERSITAS MUHAMMADIYAH GORONTALO - Syamsul Abdul Aziz; Anik Indarwati; Rahmawaty Parman (program studi psikologi, 2024)
The Effect of Optimism on Adversity Quotient in Working Students at the Universitas Muhammadiyah Gorontalo. Supervised by Anik Indarwati, as the chair and Rahmawaty Parman, as a member. This study used a quantitative approach to determine the effect of optimism on the adversary ratio of working students at the Universitas Muhammadiyah Gorontalo. The sampling technique used was simple random sampling, with a research sample of 70 working students. The data collection technique used optimism and adversity quotient questionnaires, and the research method used simple linear regression analysis. This study’s results showed a significant effect of Optimism on the Adversity Quotient, with the t count being greater than or equal to the t table (3.149 ≥ 1.670) and a significance value of 0.002 ≤ 0.05. This indicated that there was a significant influence between Optimism and Adversity Quotient. The influence given was 12.7%, and the remaining was influenced by variables other than optimism.